Study of Thermal Stability of Tetraphenanthroporphyrazine and SomeMetal Complexes By Thermogravimetric Analysis . - Abdul- ghani, Ahlam J.; M- N. Khaleel, Asmaa (Iraqi Journal of Science, 2023)
The thermal stability of previously prepared tetraphenanthroporphyrazine (TPPH2) and its complexes with VO(IV) , Co(II) , Cu(II) , Zn(II) , Mg(II) , Ca (II) ions were studied by thermogravimetric analysis (TG & DTG) at temperature range (20-1000oC). The results indicated that these compounds have a high thermal stability comparable to those of phthalocyanine compounds (PC) and higher than those of hemiporphyrazine compounds (HP) . In general metal complexes were more stable than parent ligand . Data of magnetic susceptibility and electrical conductivity were also obtained as further support for the studied compoundes .